Marketingový mix podniku - Šustrová, Barbora (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Tato diplomová práce se zabývá tématem marketingový mix podniku. Práce je rozdělena na tři části. V první části jsou vysvětleny pojmy marketingu a marketingového mixu. Druhá část popisuje vybraný podnik a analyzuje jeho současnou marketingovou situaci. Ve třetí části budou navrženy změny na zlepšení marketingového mixu a komunikace podniku.

This master‘s thesis concerns marketing mix of the company. The thesis is divided into three parts. The first part explains the concepts of marketing and marketing mix. The second part describes the selected company and analyzes its current marketing situation. In the third part, changes will be proposed to improve the marketing mix and communication of the company.
Marketing Mix of a Company
Keywords: marketing; marketing mix; komunikace; cena; SWOT analýza; marketing; marketing mix; communication; price; SWOT analysis